Unmet needs in the management of schizophrenia - Torres-González, Francisco (2017)
Studies on unmet needs during the last decades have played a significant role in the development and dissemination of evidence-based community practices for persistent schizophrenia and other severe mental disorders. This review has thoroughly considered several blocks of unmet needs, which are frequently related to schizophrenic disorders. Those related to health have been the first block to be considered, in which authors have examined the frequent complications and comorbidities found in schizophrenia, such as substance abuse and dual diagnosis. A second block has been devoted to psychosocial and economic needs, especially within the field of recovery of the persistently mentally ill. Within this block, the effects of the current economic difficulties shown in recent literature have been considered as well. Because no patient is static, a third block has reviewed evolving needs according to the clinical staging model. The fourth block has been dedicated to integrated evidence-based interventions to improve the quality of life of persons with schizophrenia. Consideration of community care for those reluctant to maintain contact with mental health services has constituted the fifth block. Finally, authors have aggregated their own reflections regarding future trends. The number of psychosocial unmet needs is extensive. Vast research efforts will be needed to find appropriate ways to meet them, particularly regarding so-called existential needs, but many needs could be met only by applying existing evidence-based interventions. Reinforcing research on the implementation strategies and capacity building of professionals working in community settings might address this problem. The final aim should be based on the collaborative model of care, which rests on the performance of a case manager responsible for monitoring patient progress, providing assertive follow-up, teaching self-help strategies, and facilitating communication among the patient, family doctor, mental health specialist, and other specialists.